Design and modeling of PEM fuel cell based on different flow fields. (15th September 2020) - Pan, Mingzhang; Li, Chao; Liao, Jinyang; Lei, Han; Pan, Chengjie; Meng, Xianpan; Huang, Haozhong
Abstract: It is necessary to investigate the designs of model to maximize the performance of proton exchange membrane fuel cell (PEMFC). In this study, a novel design and modeling method are proposed based on different flow fields. The proposed model considers the voltage losses caused by the current leakage, gas crossover, and by-product pollution. A regression analysis is conducted to study the influence of the working conditions on the accuracy. Final results showed that the coefficient of determination increased both from 0.977 to 0.952 to 0.998 at 50 °C and 70 °C, respectively. The prediction accuracy for the open-circuit voltage and low-current density is significantly improved. In addition, the prediction accuracy of different impedance materials decreases with increasing temperature and pressure. Highlights: A model for the performance prediction of PEMFCs with different flow fields. The proposed model exhibits an accurate predictability under full load. The contribution of the electron conduction resistance can be calculated. A regression analysis has been conducted to study the working conditions.